Preventive Measures in Light of the Spread of Epidemics - Mohammed, ٍٍSoulaf; Hussein, Alaa (Journal of Legal Sciences, 2023)
Countries may experience health crises that threaten their security and the safety of them public order, such as the spread of an epidemic, this matter gives the executive authority the right to take preventive measures to control matters, such as curfews and quarantine. ), (240) of the Iraqi Penal Code No. (111) of 1969. Lik ewise, the Ira00qi Public Health Law No. (89) of 1981 included administrative penalties for the same violations. The difficulty and confusion arises with the application of these texts, so we need legislative intervention by introducing an amendment to the existing legal rules or by developing a special independent law regulating criminal responsibility for spreading epidemics